Abrupt late Pleistocene ecological and climate change on Tahiti (French Polynesia). (20th June 2016) - Prebble, Matthew; Whitau, Rose; Meyer, Jean‐Yves; Sibley‐Punnett, Llewellyn; Fallon, Stewart; Porch, Nick
Abstract: Aim: To reconstruct ecological changes from the fossil record of a unique wetland on the tropical oceanic island of Tahiti, between 44.5 and 38 cal. kyrbp . Location: Vaifanaura'amo'ora, Tamanu Plateau, Punaru'u Valley, Tahiti, Society Islands, French Polynesia (17°38′S, 149°32′50″E). Methods: Fossil pollen, spores, seeds, diatoms and invertebrates were examined from a 3.7 m core consisting of Pleistocene‐aged algal sediment overlain by late Holocene peat. Results: Between 44.5 and 41.5 cal. kyrbp, Ficus trees, sub‐shrubs including Sigesbeckia orientalis L., the C4 grass species Paspalum vaginatum Sw., and extinct Pritchardia palms dominated the Vaifanaura'amo'ora wetland. This vegetation association is no longer present in the tropical oceanic Pacific islands. After 41.5 cal. kyrbp, the climate rapidly became drier and cooler with grasses, sedges and ferns dominating the vegetation. Algal sediment accumulation ceased after 38 cal. kyrbp due to prolonged dry climate conditions recorded across the Pacific Ocean. Sediment accumulation recommenced in the late Holocene. Main conclusions: The ecological responses identified from Tahiti provide evidence counter to the prevailing view that the tropical oceans buffered the ecological effects of abrupt climate changes during the last glacial period.